Spectral Features of the Solar Transition Region and Chromospheric Lines at Flare Ribbons Observed with IRIS - L. F. Wang; Y. Li; Q. Li; X. Cheng; M. D. Ding (The Astrophysical Journal Supplement Series, 2023)
We report on the spectral features of the Si iv λ 1402.77, C ii λ 1334.53, and Mg ii h or k lines, formed in the layers from the transition region to the chromosphere, in three two-ribbon flares (with X, M, and C class) observed with IRIS. All three lines show significant redshifts within the main flare ribbons, which mainly originate from the chromospheric condensation during the flares. The average redshift velocities of the Si iv line within the main ribbons are 56.6, 25.6, and 10.5 km s ^−1 for the X-, M-, and C-class flares, respectively, which show a decreasing tendency with the flare class. The C ii and Mg ii lines show a similar tendency but with smaller velocities compared to the Si iv line. Additionally, the Mg ii h or k line shows a blue-wing enhancement in the three flares, in particular at the flare ribbon fronts, which is supposed to be caused by an upflow in the upper chromosphere due to the heating of the atmosphere. Moreover, the Mg ii h or k line exhibits a central reversal at the flare ribbons but turns to pure emission shortly after 1–4 minutes. Correspondingly, the C ii line also shows a central reversal but in a smaller region. However, for the Si iv line, the central reversal is only found in the X-class flare. As usual, the central reversal of these lines can be caused by the opacity effect. This implies that, in addition to the optically thick lines (C ii and Mg ii lines), the Si iv line can become optically thick in a strong flare, which is likely related to the nonthermal electron beam heating.